2001
DOI: 10.1006/cbir.2001.0765
|View full text |Cite
|
Sign up to set email alerts
|

Gp130‐specific Antisense Oligonucleotides Inhibit Il‐6 Signal Inducing Junb Mrna Transcription in the Human Hepatoma Cell Line, Hepg2

Abstract: The biosynthesis of interleukin-6 receptor (IL-6R) and gp130 in vitro was blocked using specific antisense oligonucleotides (ASO) in HepG2 liver cells and the efficacy of various ASOs was tested on the generation of IL-6-induced junB mRNA. We used three ASOs specific for the IL-6 receptor, three specific for gp130 and a control (nonsense) oligonucleotide specific for epsilon-chain of IgE (not expressing in HepG2 cells). Our data indicate that a gp130-specific ASO, g2, was the most effective blocker of IL-6-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The mechanism by which the RPE cells undergo changes in focal contact assembly into different biochemical responses remains unclear and requires further investigation. 45,46 However, these results provided strong evidence to support the previous findings that substrate surface topography alters cell shape and . Bottom: A percentage plot of the BrdU-labeled ARPE-19 cells indicated that the cell cycles were significantly inhibited on the micropatterned surfaces.…”
Section: Discussionsupporting
confidence: 82%
“…The mechanism by which the RPE cells undergo changes in focal contact assembly into different biochemical responses remains unclear and requires further investigation. 45,46 However, these results provided strong evidence to support the previous findings that substrate surface topography alters cell shape and . Bottom: A percentage plot of the BrdU-labeled ARPE-19 cells indicated that the cell cycles were significantly inhibited on the micropatterned surfaces.…”
Section: Discussionsupporting
confidence: 82%
“…Although the IL-6 receptor gp80 mRNA was not significantly increased in MIA-MSLN cells, there was a significant, albeit small, increase in the gp130 level ( Figure 5B). gp130 signaling in concert with sIL-6R was found to be more important in IL-6 signaling than the membrane-bound IL-6R in hepatoma (37). The discovery that MIA-MSLN cells have increased sIL-6R is significant.…”
Section: Discussionmentioning
confidence: 97%